Prediction model for labour dystocia occurring in the active phase - Yanqing Liu; Qingquan Gong; Yuhong Yuan; Qi Shi (Taylor & Francis Group, 2023)
To establish and verify a model for labour dystocia occurring in the active phase, this study retrospectively analysed the clinical data of primiparas with singleton cephalic full-term foetuses, who had delivered after a trial of labour. The Chi-square test, t-test, Mann-Whitney U test and multivariate logistic regression analysis were used for statistical analysis. Based on the model a nomogram was established using the R programming language. Multivariate logistic regression analysis showed that the foetal abdominal circumference, premature rupture of membranes (PROM), prolonged latent phase, foetal station and foetal position at the early stage of the active phase were independent factors influencing labour dystocia occurring in the active phase. The established model could effectively and accurately support clinicians in the early identification of labour dystocia to improve maternal and infant outcomes.Impact statement What is already known on this subject? Labour dystocia occurring during the active phase of the first stage, is the most commonly diagnosed as labour aberration. Previous studies have suggested that maternal age, body mass index, macrosomia and abnormal foetal position are the independent risk factors for labour dystocia. However, only the risk factors were reported, and few prediction models were established. What do the results of this study add? This study uses data in the real world to establish a prediction model of full-term singleton primipara with labour dystocia occurring in the active phase by logistic regression analysis. Foetal abdomen circumference, PROM, prolonged latent phase, the foetal station and foetal position at the early stage of the active phase are independent factors influencing labour dystocia that occurs in the active phase. In addition, a nomogram is established as a visual graph to predict the probability of it. What are the implications of these findings for clinical practice and/or further research? The nomogram based on the predictive model discarded complicated calculations and presented an easy visual graph-based method to predict the probability of labour dystocia occurring in the active phase. It helps to introduce interventions that could reduce the CS rate and occurrence of adverse maternal and foetal outcomes to ensure the safety of mothers and infants.